The School Environment as a Contextual Learning Strategy: Its Impact on Junior High School Students' Interest in Learning Biology - Zulfana Zulfana; Musdalifah Nurdin; Raya Agni (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to examine the significant impact of utilizing the school environment as a learning resource on students’ interest in learning Biology among seventh-grade students at SMPN 10 Sigi. The research applied a quasi-experimental design involving 55 students, divided into an experimental class and a control class. Data collection techniques included observation of students’ learning interest, interviews with the science teacher, and a post-test to assess academic understanding. Instruments used in this study comprised observation sheets, structured interview guides, and post-test items. Both descriptive and inferential statistical methods were used to analyze the data. The findings revealed a substantial difference between the two groups. The experimental class, which engaged in outdoor and environment-based learning activities, achieved an average interest score of 92.5% (categorized as Very Good), while the control class, which received conventional classroom instruction, scored 76.2% (categorized as Good). Students in the experimental group showed increased enthusiasm, curiosity, and active participation, particularly during explorative activities related to biodiversity around the school grounds. These results confirm that integrating the school environment into the learning process not only enhances student engagement but also fosters a deeper understanding of scientific concepts. The study concludes that effective use of the school environment can significantly increase students’ interest and motivation in learning science, especially in rural or under-resourced educational settings.